Relationship between Concentration of Nitrate, Phosphate, and Silicate with Abundance of Diatom Aroundthe Waters of Tapian Nauli North Sumatera Province - Windarti Nofriyan Nengsih; Irvina Nurrachmi; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted from January to February 2015 in the coastal waters of Tapian Nauli, North Sumatera Province. The samples were analyzed in the Laboratory of Marine Chemistry of Marine Science Department, University of Riau. The research aimed to determine the relationship between nutrients (nitrate, phosphate and silicate) with abundance of diatoms. This research used survey method and the file were analyzed by using linear regression analysis. The results showed concentrations of nitrate ranged 1.18 to 1.27 mg/l, phosphate 0.04 to 0.35 mg/l, and silicate 0.46 to 0.48 mg/l. The diatoms found during the research were consisting 13 species. The highest abundance of diatoms was recorded in the station III (48080 ind/l), and the lowest was in the station I (1314 ind/l). Relationship between concentration of nitrate, phosphate and silicate with the abundance of diatoms showed a weak connection.Keywords: Nitrate, Phospate, Silicate, Diatom, Tapian Nauli